COMPLETING THE CIRCLE: TOWARDS THE ACHIEVEMENT OF IND-EQUITY- A CULTURALLY RELEVANT HEALTH EQUITY MODEL BY/FOR INDIGENOUS POPULATIONS - Bernice Downey (York University Libraries, 2020)
Health equity is defined in ways that espouse values of social justice and benevolence and is held up as an ideal state achievable by all. However, there remains a troubling gap in health outcomes between Indigenous Peoples and other Canadians. Public health stakeholders aspire to 'close the gap' and 'level the gradient' to reduce inequities though the implementation of various health equity focused strategies. The Truth and Reconciliation Commission of Canada echoes this objective and calls for self-determining structural reform to address health inequity for Indigenous Peoples. This paper proposes an IND-equity model as a reconciliation inspired response that upholds Indigenous self-determination and is informed by diverse Indigenous ways of knowing.  When adopting this model, the goal is to complete the circle and foster wholistic balance. Further development and implementation of an IND-equity model requires advocacy by all health practitioners. Nurses hold potential to lead and engage in structural reform through an Indigenous health ally role.